Population Genetics and Phylogeography of Bigeye Tuna in Moluccas Seas, Indonesia - Nebuchadnezzar Akbar; M. Irfan; Muhammad Aris (Marine Science Department Diponegoro University, 2018)
The bigeye tuna (Thunnus obesus) is a migratory fish which can be found in the Atlantic, Indian and Pacific oceans. This fish has a commercial value and has been exploited worldwide including in Indonesia. The exploitation might affect the genetic diversity and population structure. The fact that the population stock resource is abundant and following fishing activities are increasing, study on population genetic and phylogeography canbe used as information to determine the status of the fish population based on genetic data. The study was conducted to investigate population genetic, and phylogeography of bigeye tuna in the North Moluccas and South Mollucas Seas, Indonesia. A total of 60 tissue bigeye tuna samples were collected from two study sites. The samples were amplified using mitochondrial DNA control region. Within population genetic diversity was revealed of 0.985 and 1.00 in North Moluccas and in south Moluccas, respectively, while between populations was 0.989. The genetic distance within population of North Moluccas (0.029) and South Mollucas (0.24) was very low, and all population was 0.027. The genetic distance between population of North Mollucas and South Mollucas was 0.025, South Mollucas and all population was 0.023, and all population with Norht Mollucas was 0.027. The genetic distance of North Mollucas and Pacific Ocean was 0.029, South Mollucas and Pacific Ocean was 0.023, North Mollucas, South Mollucas and Indian Ocean was 0.32. The Fst value between populations (0.990) showed that the two populations were not genetically different. A similar result showed from the phylogenetic trees analysis which individual of bigeye tuna was randomly clustred between North Moluccas and South Mollucas population, indicating that they were genetically close and from the same population. The population bigeye tuna from the North Mollucas and the South Mollucas exhibits no apparent phylogeographic distribution.